Peran Kepemimpinan Kepala Sekolah Dalam Meningkatkan Kinerja Guru Pada Sd Negeri 3 Towea Kecamatan Towea Kabupaten Muna - Nafwati, Nafwati; Batara, Suriyani Bunga; Nurjannah, Nurjannah (Universitas Halu Oleo, 2020)
The purpose of this study was to determine the Principal's Leadership Role in Improving Teacher Performance in Towea 3 Primary School Towea District Muna District. The method used in this research is descriptive qualitative method. The informants in this study were all teachers / staff of Towea 3 Primary School, totaling 6 people as respondents. In addition, 1 informant was used, namely the School Principal. Data collection techniques using field observations, interviews, and documentation. The results showed that the role of principal leadership in improving teacher performance at SD Negeri 3 Towea can be assessed from three indicators, namely the role as interpersonal, information, and decision making. The role of the principal's leadership as interpersonal can be concluded by several indicators, namely as a symbol of the organization (figurehead), as a leader (leader) and as a liaison (liasion). The leadership role of the principal as informational is said to be good. This can be seen as the role of monitor and spokesperson where the principal disseminates information to teachers at SD Negeri 3 Towea. The role of the principal as a decision-making is said to be still not optimal in this case as the role of entrepreneur where the principal makes decisions by involving teachers and there is no assertiveness. As a negotiator's role (negotiation), it is said to be maximal, where the principal always negotiates with other organizations.